2011
DOI: 10.1128/cvi.05285-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Six Commercial Point-of-Care Tests for Diagnosis of Acute Dengue Infections: the Need for Combining NS1 Antigen and IgM/IgG Antibody Detection To Achieve Acceptable Levels of Accuracy

Abstract: ). The median number of days of fever prior to admission sample collection was 5 days (interquartile range, 3 to 7 days). Sensitivity and specificity of the NS1 antigen tests ranged from 49 to 59% and from 93 to 99%, respectively, and sensitivity and sensitivity of the IgM antibody test ranged from 71 to 80% and from 46 to 90%, respectively. Combining the NS1 antigen and IgM antibody results from the Standard Diagnostics Dengue Duo test gave the best compromise of sensitivity and specificity (93% and 89%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
120
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(145 citation statements)
references
References 15 publications
17
120
2
1
Order By: Relevance
“…As the samples studied were "day of admission samples" from adults, there may be some variation in the timing of the individual samples in relation to disease onset. The PCR methodology used here would be more sensitive for samples from very early after fever onset [18], while both NS1 and serological testing would be more sensitive for samples taken later after fever onset [19]. This would possibly account for the samples detected by PCR, but not by serology or NS1 testing (samples collected early after fever onset) and samples positive by serologic/NS1 but negative by PCR (samples collected later in the course of the fever).…”
Section: Discussionmentioning
confidence: 99%
“…As the samples studied were "day of admission samples" from adults, there may be some variation in the timing of the individual samples in relation to disease onset. The PCR methodology used here would be more sensitive for samples from very early after fever onset [18], while both NS1 and serological testing would be more sensitive for samples taken later after fever onset [19]. This would possibly account for the samples detected by PCR, but not by serology or NS1 testing (samples collected early after fever onset) and samples positive by serologic/NS1 but negative by PCR (samples collected later in the course of the fever).…”
Section: Discussionmentioning
confidence: 99%
“…21 Another study evaluating four rapid IgM assays, found a more consistent range of sensitivities (71-80%) but had a wider range of specificities (46-89%). 6 Non-structural protein 1 assays performed comparably, with sensitivities of 49-59% and specificities of 93-99%. 6 Although rapid assays may possess slightly better outcome measures than the TT, the cost of rapid diagnostic assays must be considered in countries such as Peru, where the average annual per capita health expenditures are US $269.…”
Section: Discussionmentioning
confidence: 99%
“…6 Non-structural protein 1 assays performed comparably, with sensitivities of 49-59% and specificities of 93-99%. 6 Although rapid assays may possess slightly better outcome measures than the TT, the cost of rapid diagnostic assays must be considered in countries such as Peru, where the average annual per capita health expenditures are US $269. 22 Another approach to dengue diagnosis uses data normally collected during a patient's admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined sensitivity of the dengue NS1 antigen and immunoglobulin M (IgM) antibody test increases to 89.9-92.9%, with a specificity of 75.0-88.8%. 5 The use of such tests on patients with a low pre-test probability could result in an increase in false-positive results, leading to dilemmas in clinical assessment and delays in initiating appropriate management for the individual patient.…”
Section: Introductionmentioning
confidence: 99%